THE IMPACT OF HEDONIC SHOPPING MOTIVATION ON IMPULSIVE BUYING DECISIONS : A SYSTEMATIC LITERATURE REVIEW APPROACH IN THE CONTEXT OF MODERN RETAIL - Tri Imaliya (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This work integrates the outcomes of five studies examining the influence of hedonic shopping motivation on impulse buying within the context of modern retailing in Indonesia. The analysis reveals at least some common patterns regarding the impact of anthropocentric motivation (shopping enjoyment, trend watching, and routine escape) on impulse buying, albeit with contextual differences. The studies on students (Hidiani & Rahayu, 2021) and Popshop consumers (Yusda & Nilasari, 2022) confirmed the positive impact of hedonic shopping motivation (β = 0.276–0.735), moderated by shopping lifestyle and visual merchandising. On the other hand, research at Miniso Tunjungan Plaza (Pranggabayu & Andjarwati, 2022) found that the store atmosphere had a negative impact (β = -0.062), as it was hypothesized that the too rigid store atmosphere decreases spontaneous purchasing. Sendi & Zaini (2024) reported in Samarinda that sales promotion had no significant impact (β = 0.071), and that motivation and lifestyle dominated. In the sociopolitical context, browsing social media enhances the effect of hedonic motivation on online impulse buying among Gen-Z (β=0.297) (Pratama et al., 2023). This interplay of intrinsic (hedonism) and extrinsic (store environment or digital media) elements presents a complex landscape that stimulates impulsive buying behavior.Practically, these are suggestions to improve hedonic experiences through immersive design, limit overly aggressive promotions, and vary visual tactics based on age cohort. Such an integration contributes to esthetics in marketing by showing the need of a more contextual view of the problem regarding impulse buying in relation to hybrid retailing.